Silicosis and autoimmunity. Issue 2 (April 2017) - Lee, Suni; Hayashi, Hiroaki; Mastuzaki, Hidenori; Kumagai-Takei, Naoko; Otsuki, Takemi
Abstract : Purpose of review: Of the various environmental, occupational, and medical substances that cause dysregulation of autoimmunity, the effects and causative mechanisms of silica particles and asbestos fibers are discussed in this review. Recent findings: With respect to silica, many epidemiological studies have shown a significant association between silica exposure and the occurrence of autoimmune diseases. Although the importance of the NACHT, LRR and PYD domains-containing protein 3 (NALP3) inflammasome as the initial immune reaction against silica particles has been identified, the mechanisms involved that lead to various autoimmune diseases in patients exposed to silica remain largely unknown. Silica can activate various immune cells and investigation of the associated imbalance of regulatory T cells, responder T cells as well as Th17 cells might be key in furthering our understanding of silica-induced autoimmune alterations. On the other hand, asbestos exposure shows less association with autoimmune diseases. However, interesting findings pertaining to the detection of antiendothelial and mesothelial cell antibodies in asbestos-exposed patients have been reported. Summary: Taken together, further investigations may contribute in delineating the mechanisms involved in environmental factor-induced modification of autoimmunity.